Pengaruh Terpaan Kampanye #2019GantiPresiden dan Persepsi Masyarakat Tentang Program Kerja Pasangan Capres Prabowo Sandi Terhadap Minat Memilih Prabowo Sandi Pada Pilpres 2019 di Sumatera Barat - Rahmi Hayati; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Social media is considered to be the most effective in spreading issues so that it becomes viral in the society. One of the massive issues disseminated on social media is the issue related to changing the president in 2019 to bring up the # 2019GantiPresiden’s hashtag, which has been mentioned more than 1 million times on twitter during the period 1 July to 31 December 2018. The emergence of this hashtag aims to gain public support for presidential candidate Prabowo Subianto. However, the electability of Prabowo Subianto in West Sumatra according to the results of a survey from Indo Barometer at the end of January 2018 actually declined compared to the 2014 presidential election which amounted to 19.1% while Jokowi's elecability rise compared to the 2014 presidential election, which was 32%. In addition to information factors from social media, another factor that also influences someone's interest in choosing a presidential candidate is through their perception of work programs carried out by the presidential candidates concerned. This study aims to determine whether there is an influence of #2019GantiPresiden campaign exposure on social media and public perceptions of the Prabowo Sandi presidential candidate's work program toward the interest in choosing Prabowo Sandi in the 2019 presidential election in West Sumatra. This research is an explanatory quantitative research. The theory used in this study is the Social Media Framework Theory to verify the influence of #2019GantiPresiden campaign exposure on social media toward select interests and Interpersonal Theory and Public Opinion to verify the influence of public perceptions of Prabowo Sandi's presidential candidate's work program on people's interest in West Sumatra. The sampling technique using nonprabability sampling was carried out by purposive sampling with total sample of 50 people with the criteria is West Sumatra citizens aged 17-25 years and exposed to # 2019 GantiPresident campaign exposure on social media. Testing is done using the Ordinal Regression Test. The results showed that there was no effect on # 2019GantiPresiden campaign exposure toward interest in choosing Prabowo Sandi in West Sumatra with a significance of 0.241 over the significance standardization of 0.05. This shows that campaign exposure #2019GantiPresiden on social media doesn’t affect the interest of the people of West Sumatra to choose Probowo Sandi. The results also showed that there was an influence of the public perception of the work program on the interest in choosing Prabowo Sandi in the 2019 Presidential Election in West Sumatra at 26.5%. The remaining 73.5% is influenced by other factors not examined in this study. Correlation between variables shows significance of 0.004. This shows that there is an influence of the public perception of the work program toward the interest in choosing Prabowo Sandi in the 2019 Presidential Election in West Sumatra. For further research, it is expected to be able to examine more about other factors beyond the factors studied which can influence a person's interest in choosing a leader.